Nonlinear methods of heart rate variability analysis in diabetes - Ricci Vitor, Ana Laura [UNESP]; de Souza, Naiara Maria [UNESP]; Regueiro Lorenconi, Roselene Modolo [UNESP]; Pastre, Carlos Marcelo [UNESP]; Abreu, Luiz Carlos de [UNESP]; Valenti, Vitor Engrácia [UNESP]; Marques Vanderlei, Luiz Carlos [UNESP] (Drunpp-sarajevo, 2012)
Background: The autonomic dysfunction stands out among the complications associated to diabetes mellitus (DM) and may be evaluated through the heart rate variability (HRV), a noninvasive tool to investigate the autonomic nervous system that provides information of health impairments and may be analyzed by using linear and nonlinear methods. Several studies have shown that HRV measured in a linear form is altered in DM. Nevertheless, a few studies investigate the nonlinear behavior of HRV. Therefore, this study aims at gathering information regarding the autonomic changes in subjects with DM identified by nonlinear analysis of HRV.Methods: For that, searches were performed on Medline, SciELO, Lilacs and Cochrane databases using the crossing between the key-words: diabetic autonomic neuropathy, autonomic nervous system, diabetes mellitus and heart rate variability. As inclusion criteria, articles published on a period from 2000 to 2010 with DM type land type II population which assessed the autonomic nervous system by nonlinear indices HRV were considered.Results: The electronic search resulted in a total of 1873 references with the exclusion of 1623 titles and abstracts and from the 250 abstracts remaining, 8 studies were selected to the final analysis that completed the inclusion criteria.Conclusions: In general, the analysis showed that the nonlinear techniques of HRV allowed detecting autonomic changes in DM. The methods of nonlinear analysis are indicated as a possible tool to be used for early diagnosis and prognosis of autonomic dysfunction in DM.
Keywords: autonomic nervous system; diabetic autonomic neuropathy; diabetes mellitus